Compression Test for Diagnosis of Phalangeal Fracture; a Letter to Editor - Mohamad Karimi, Naser; Zeinali.N, Faeze (Archives of Academic Emergency Medicine, 2019)
Physical examination is the most important procedure for examining traumatized patients and ruling out possible bone fractures. Edema, deformity, ecchymosis, tenderness on trauma location, and limited bone movement are among the signs of fracture. The diagnosis is documented by plain radiography. The number of false positive cases in this test increase in the presence of soft tissue injury along with bone damage. In this case, a great number of X-rays will be taken daily and many patients will be exposed to radiation, unnecessarily (1). The question to be fully answered is whether all cases of trauma and pain require radiographs or not?